Fibre optic interconnecting devices and passive components. Performance standard. Simplex patch-cord style single-mode fibre wavelength selective devices with cylindrical ferrule connectors for category C. Controlled environment Part 043-02, (17th October 2022) - British Standards Institution,
No abstract available